Field survey data on the effectiveness of agrometeorological services for smallholder farmers in Niger - M. Bacci; C. Zini; O.A. Idrissa; S. Burrone; A. Tsayabou; S.S. Maïga; A.A. Sitta; V. Tarchiani (Data in Brief, 2023)
The dataset contains the answers of smallholder farmers to a semi-structured field survey and the 2020 yield plot measurements conducted in 8 municipalities of the Dosso and Tillabéri regions in Niger. It is a systematic sampling of about 320 questionnaires and 192 yield plot samples equally distributed in eight municipalities of intervention. The dataset contains several pieces of information about the uptake and the impacts of a tailored climate service (CS) produced by the National Meteorological Service (NMS) and disseminated through a network that involves Ministry of Agriculture extension services at the municipal level developed in the context of the AdaptatioN Au changement Climatique, prévention des catastrophes et Développement agrIcole pour la sécurité Alimentaire du Niger (ANADIA) Project. The material gathered by the survey gives a picture of the preferences of local farmers in the broadcasting of climate services information and their consequent strategical and tactical decisions in farm practices. Moreover, the survey investigates the preferences regarding the information that farmers would like to receive during the cropping season. Furthermore, the measurement of yield and its relation to the farmers’ access to climate information and participation in training initiatives gives an indication of the impact of the CS on agricultural production in these regions.The dataset could benefit further studies and investigations about CSs for smallholder farmers in semi-arid regions.This article is a co-submission of the article: “Effectiveness of agrometeorological services for smallholder farmers: the case study in the regions of Dosso and Tillabéri in Niger” submitted to the journal Climate Services.